Achieving research impact through co-creation in community-based health services: literature review and case study - Greenhalgh, T; Jackson, C; Shaw, S; Janaiman, T (Wiley, 2016)
Context Co-creation – collaborative knowledge generation by academics working alongside other stakeholders – reflects a ‘Mode 2’ relationship (knowledge production rather than knowledge translation) between universities and society. Co-creation is widely believed to increase research impact. Methods We undertook a narrative review of different models of co-creation relevant to community-based health services. We contrasted their diverse disciplinary roots and highlighted their common philosophical assumptions, principles of success and explanations for failures. We applied these to an empirical case study of a community-based research-service partnership led by the Centre of Research Excellence in Primary Health Care Reform at the University of Queensland, Australia. Findings Co-creation emerged independently in several fields including business studies (‘value co-creation’), design science (‘experience-based co-design’), computer science (‘technology co-design’), and community development (‘participatory research’). These diverse models share some common features, which were also evident in the case study. Key success principles included [a] a systems perspective (assuming emergence, local adaptation and non-linearity); [b] framing of research as a creative enterprise with human experience at its core; and [c] an emphasis on process (how the program is framed; the nature of relationships; and governance and facilitation arrangements, especially the style of leadership and how conflict is managed). In both the literature review and the case study, co-creation ‘failures’ could often be tracked back to abandoning (or never adopting) these principles. All co-creation models made strong claims for significant and sustainable societal impacts as a result of the adaptive and developmental research process; these were illustrated in the case study. Conclusion Co-creation models have high potential for societal impact but depend critically on key success principles. To capture the non-linear chains of causation in the co-creation pathway, impact metrics must reflect the dynamic nature and complex interdependencies of health research systems and address processes as well as outcomes.